Juvenile gilthead sea bream immune response against RGNNV or RGNNV/SJNNV infections - Gémez-Mata, Juan; Moreno Garcia, Patricia; Álvarez-Torres, Daniel; García-Rosado, Esther; Béjar-Alvarado, Julia; Alonso-Sánchez, María del Carmen (Sociedad Española de Virología, 2024)
Viral nervous necrosis is one of the main threats for the aquaculture. It is caused by the nervous necrosis virus (NNV), with a genome composed of two positive-sense, ssRNA segments: RNA1, encoding the viral polymerase; and RNA2, encoding the capsid protein. NNV have been clustered into four species:RG, SJ, BF and TP. In addition, reassortment between RG and SJ has also been detected. NNV can affect a wide range of fish species; however, not all viral species are equally virulent to all fish species; this issue is relevant concerning European sea bass and gilthead sea bream, which are frequently co-cultured. Sea bass is susceptible to RG, whereas RG/SJ cause low mortality in this species. On the contrary, RG/SJ cause high mortality in sea bream and this fish is reluctant to RG infections. The outcome of viral infections depends on the specific virus-host interaction. Understanding the mechanisms responsible for this differential interaction is crucial to control viral diseases in aquaculture. This study focuses on the analysis of the immune gene transcription in brain of 3g sea bream experimentally infected with NNV isolated from sea bass (Dl, RG) or sea bream (Sa, RG/SJ). We have analysed genes suggested to be relevant in controlling RG infection in sea bass: inflammatory, apoptotic, stress and IFNI. Mortalities were not recorded in any group for 30 days, and the quantification of viral genome evidenced that only Sa replicated in sea bream brain. Principal component analysis clustered samples according to the viral isolate from 1 day post-infection onwards, and evidenced differences in the immune response against both viruses. Sea bream response against Dl is characterized by a higher rtp3 transcription early after the infection, a longer-lasting transcription of the antinflammatory gene il10 and a stronger induction of casp1 and hsp70. These genes should be targets for future studies in order to elucidate their role in hampering the replication of RG in sea bream
Keywords: Peces - Virus; Betanodavirus; Dorada; Respuesta inmune